Effect of Upland Rice Varieties on Relative Composition of Weeds in Jharkhand - Barla, Sheela; Upasani, R. R. (International Journal of Bio-resource and Stress Management, 2018)
Weed management in upland rice production is a major constraint in reducing rice yield in Jharkhand state. Studies were conducted during the wet cropping season of 2011 and 2012 at Zonal Research Station, East Singhbhum under upland ecology to assess and identify crop parameters responsible for competitiveness of rice varieties. Total thirteen upland varieties including ten improved and three traditional varieties were tested under weedy and weed free conditions. The major weeds found in the experimental plot were Bulbostilis barbata, Ludwigia parviflora, Cyperus rotundus, Alternanthera sessilis and Cynodon dactylon The results indicated that rice varieties differed in their competitiveness against weeds. Bulbostilis barbata was found as a major weed at 25, 50 and 75 DAS with average relative composition of 44.39, 41.37 and 46.82% in weedy condition, while 32.15, 30.46 and 22.92% under two hand weeding at 20 and 40 days after sowing. The varieties Vandana and Anjali were found to be most competitive and productive, whilst among local varieties, Tanrbhojna though competitive in suppressing weeds but was not much productive. Maximum yield loss of 29.86% occurred when no weeding was performed irrespective of rice varieties. Among different improved rive varieties BVD-110, Vandana and Anjali recorded yield loss to the tune of 5.24, 7.01 and 8.6% respectively. However, traditional varieties Asanleva, Balibhojna and Tanrbhojnarecorded yield loss to the extent of 4.59, 4.83 and 6.02% indicating weed suppressing ability compared to others.